Treatment of Pregnant Patients With Orthopaedic Trauma. Issue 5 (May 2017) - Tejwani, Nirmal; Klifto, Kevin; Looze, Christopher; Klifto, Christopher Scott
Abstract : Fracture management in pregnant patients is challenging. Anatomic and physiologic changes in pregnancy increase the complexity of treatment. Maternal trauma increases the risk of fetal loss, preterm birth, placental abruption, cesarean delivery, and maternal death. Initial resuscitation and treatment in a facility equipped to handle the orthopaedic injury and preterm births are paramount. Pelvic and acetabular injuries are potentially life threatening. The benefits and risks of surgical treatment must be carefully considered. The risks posed by anesthetic agents, antibiotic agents, anticoagulant agents, and radiation exposure must be understood. Positioning of the patient can affect the viability of the fetus. If surgery is necessary, the left lateral decubitus position decreases fetal hypotension. A specialized team including an obstetrician, perinatologist, orthopaedic surgeon, general trauma surgeon, critical care specialist, emergency medicine specialist, anesthesiologist, radiologist, and nurse must collaborate to improve maternal and fetal outcomes.